Judy Moody - McDonald, Megan; Reynolds, Peter (Miami, FL : Alfaguara, 2004)
Third grader Judy Moody is in a first day of school bad mood until she gets an assignment to create a collage all about herself and begins creating her masterpiece, the Me collage.
530
Accelerated Reader
Keywords: First day of school -- Juvenile fiction; Schools -- Juvenile fiction; Emotions -- Juvenile fiction; Primer día de escuela -- Novela juvenil; Escuelas -- Novela juvenil; Emociones -- Novela juvenil